Confucius' conception of disobedience in the name of civilization - Satrawat, Rachod (2013)
Civil obedience becomes one of the main polemical issues in political philosophy especially in the chaotic contemporary world.In western culture, the philosophers like Socrates as well as the non-violent activists like Gandhi and Martin Luther King are globally considered as the main figures that represent the multifarious approaches on this peaceful socio-political movement.In their perspective, civil disobedient is the way to react against the some "unjust" laws and rebuilds the social order implying the social justice. What should not be unnoticeable is their foundation: civil disobedience bases on citizen's will,justice and common "good".On the contrary, in classical Chinese philosophy, civil disobedience seems to be one of absent issues particularly in Confucianism.In this school, the filial piety is so highly accentuated that the disobedience is totally marginalized or treated as prohibition.The children need to "obey" the parents will and maintain the stability of the family and the cultural rites.My main purpose is to re-read Confucianism in the light of the original Confucian text and reconceptualise the disobedience in the Confucius Analects which can be called "disobedience in the name of civilization".In this text, Confucius' main philosophical project is to critique the fraudulent act of the "politician" in his time, criticize the people's decadent morality and restore the social order susceptible to the perfection in the Ancient time.It seems that his philosophical proposal requires as primordial condition the fundamental virtue: the filial piety.Although this moral conduct is necessary for the stable social order, it doesn't imply the unconditional obedience or the absolute subjection.In Confucius Analects, many passages represent paradoxically the disobedient obedience and the obedient disobedience from the most basic unit of the society to the highest class of the hierarchy. What is noteworthy in this way of "disobedience" is the question of foundation and its orientation.In the other word, in western culture, civil disobedience is founded on the people's will, justice and common good while Confucius disobedience is centered on the openness of civilization demand: it is acceptable that the children need to obey the parents will but they are also obliged to "educate" their parents volition as well.In the same token, the inferior subject, in the political realm, needs to react politely against the superior or governor's wrong decision.This can maintain the pulchritude of the ancient civilization and fulfill its opened possibilities towards the future.In conclusion, the Confucius conception of "disobedience in the name of civilization" provides the new contribution to political and philosophical milieu.In the western civilization, civil disobedient is formulated on the ancestor need to be recognized.In the other words, civilization can be perceived and conceived as the foundation of disobedience.In this point of view, everyone needs to obey in the disobedient way and express their disobedience politely or "obediently" so that they can react against political evil and social fraudulence and stabilize the mutual relation in the civilization foundation of people's will, justice and common good but in ancient Chinese civilization the value of the ancestor need to be recognized.In the other words, civilization can be perceived and conceived as the foundation of disobedience. In this point of view, everyone needs to obey in the disobedient way and express their disobedience politely or "obediently" so that they can react against political evil and social fraudulence and stabilize the mutual relation in the civilization.